THE TECHNIQUE AND TRANSLATION QUALITY OF FACE THREATENING ACTS (FTAS) IN ANNE OF GREEN GABLES - Yurike Suhertian Poyungi; Dessy Dwijayanti (Prodi Sastra Inggris UKI, 2024)
Abstract This study is a descriptive qualitative that aims to describe the types of Face threatening Acts (FTAs). Besides, this study also aims to analyze the translation techniques and the translation quality of a novel entitles Anne of Green Gables. It is found that 37 utterances which accommodates FTAs in the orientation structure of the novel and involves 4 types of FTAs, they are bald on record (18 data), off record (6 data), FTA using positive politeness (3 data), and FTA using negative politeness (10 data). The translation techniques used to translate the FTAs are established equivalence, linguistic amplification, discursive creation, addition, borrowing, reduction, and modulation. Established equivalence is the most dominant techniques. Therefore, the translation quality of FTAs in Anne of Green Gables is accurate, acceptable, and readable.